Targeting the Poor: A Macroeconomic Analysis of Cash Transfer Programs - Tiago C. Berriel; Eduardo Zilberman (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2012)
This paper introduces cash transfers targeting the poor in an incomplete marketsmodel with heterogeneous agents facing idiosyncratic risk. These transfers change the degree of insurance in the economy and affect precautionary motives asymmetrically,leading the poorest households to decrease savings proportionally more than their richer counterparts. In a model economy calibrated to Brazil, once the cash transfer program is adopted, wealth inequality and social welfare increase, poverty decreases,while employment and income inequality remain about the same. Imperfect access to financial markets is important for these results, whereas whether the program is funded with lump sum or distortive taxes is not.
Keywords: D31; E21; H31; 330; Unvollkommener Markt; Armut; Öffentliche Sozialleistungen; Vorsichtssparen